2015
DOI: 10.1177/1088357615588523
|View full text |Cite
|
Sign up to set email alerts
|

Early Numerical Competencies in 4- and 5-Year-Old Children With Autism Spectrum Disorder

Abstract: Studies comparing mathematical abilities of children with autism spectrum disorder (ASD) and typically developing children are hitherto scarce, inconclusive, and mainly focusing on elementary school children or adolescents. The present study wants to gain insight into the foundation of mathematics by looking at preschool performances. Five early numerical competencies known to be important for mathematical development were examined: verbal subitizing, counting, magnitude comparison, estimation, and arithmetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Studies predominantly indicated deficits in text generation abilities for autistic individuals, while overall intact or slightly impaired spelling skills were reported ( Finnegan and Accardo 2018 ; Mayes and Calhoun 2003a , 2003b ). Similarly, the majority of autistic individuals exhibited average competencies in mathematics, such as mathematical problem solving, compared to non-autistic peers or to the norm population in previous research ( Chiang and Lin 2007 ; Titeca et al 2017 ; Troyb et al 2014 ).…”
Section: Introductionmentioning
confidence: 55%
“…Studies predominantly indicated deficits in text generation abilities for autistic individuals, while overall intact or slightly impaired spelling skills were reported ( Finnegan and Accardo 2018 ; Mayes and Calhoun 2003a , 2003b ). Similarly, the majority of autistic individuals exhibited average competencies in mathematics, such as mathematical problem solving, compared to non-autistic peers or to the norm population in previous research ( Chiang and Lin 2007 ; Titeca et al 2017 ; Troyb et al 2014 ).…”
Section: Introductionmentioning
confidence: 55%
“…For this reason, it is necessary to examine the variability of magnitude representation in this population. As mentioned before, previous studies have shown inconsistent findings when comparing magnitude representation precision between groups with and without ASC (Aagten-Murphy et al, 2015;Bangel et al, 2014;Hiniker et al, 2016;Titeca et al, 2014Titeca et al, , 2015Titeca et al, , 2017, which implied the large variability of magnitude representation in individuals with ASC. However, this variability has not been quantitatively compared between groups, hence it is unknown whether those with ASC have comparable or even larger variability than their peers without ASC in magnitude representation.…”
Section: Mental Magnitude Representation In Individuals With Ascmentioning
confidence: 88%
“…a more imprecise magnitude representation) than their peers without ASC. However, other studies found no group differences in preschoolers (Titeca et al, 2014, 2015, 2017), school-aged children (Gagnon et al, 2004), or adults (Bangel et al, 2014). These findings suggested that individuals with and without ASC have comparable magnitude representation abilities (Titeca et al, 2014, 2015, 2017).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A study summarizing the literature shows they may have lower math ability than the general population (Chiang & Lin, 2007). In contrast, some studies find no difference in math abilities between autistic individuals and their typically developing peers across a wide age range, from preschools (Titeca et al, 2015;Titeca et al, 2014) and school-age children (May et al, 2015;Mayes & Calhoun, 2007) to adults (Goldstein et al, 2001;Tops et al, 2017). A study finds that autistic students excel in math, with scores of 1.3 standard deviations (SDs) above the normed sample on overall math proficiency (Assouline et al, 2012).…”
mentioning
confidence: 99%